Pro Kontra Ulama Terhadap Konsep Munasabah Al-Qur’an - Diaz, Ahmad Diaz Makmur; Amrullah; Akram; Kulle, Haris; Umar, Ratnah (Program Studi Ilmu Al-Quran dan Tafsir, 2025)
Abstract: This paper discusses the Pro Ulama regarding the concept of Munasabah in the Qur'an. The main issue of this study is to identify and analyze the differences in opinion and arguments among scholars regarding the legitimacy and application of Munasabah in revealing the connections between verses in the Qur'an. This research employs a literature review method with a content analysis approach applied to various sources, including tafsir texts, academic articles, and works by scholars discussing Munasabah. The theoretical framework centers on the importance of Munasabah as a tafsir methodology, while also highlighting the dynamics of thought within the Islamic scholarly tradition. The results of the study show a variety of views, ranging from scholars who positively accept and widely appreciate Munasabah, to those who tend to underestimate or even reject certain aspects of it. This diversity of thought reflects the plurality of interpretations and approaches in understanding the Qur'an, where each perspective remains grounded in the fundamental principles of sharia and their respective scientific foundations.